Social Interaction Strategies of Primary Teachers in Inclusive Teaching in Secondary Schools: Strategi Interaksi Sosial Guru Perdana dalam Pengajaran Inklusif di Sekolah Menengah - Jamaludin, Nazrah; Shaffeei, Kama (Jurnal Pendidikan Bitara UPSI, 2023)
The landscape of Inclusive Education is now largely shaped by various international declarations to ensure that the agenda and its implementation remain relevant in the education system. There is no doubt that there are still various constraints throughout its implementation that require the best and most effective strategy. Through the design of a qualitative study, the researcher focuses on strategies to face challenges in the social interaction of teachers in inclusive classes in secondary schools in Selangor. A pilot study was carried out on three study participants at school A. Meanwhile, the actual study involved seven study participants from school B selected by sampling to participate in interview and observation sessions that lasted for six months. Semi-structured interview protocols and non-participant observation checklists are instruments used by researchers in the field. The findings of the study were analyzed using the Atlas.ti software 22. The results of the study found four themes that emerged in the strategy of dealing with the social interaction challenges of prime teachers in teaching, namely teachers diversifying approaches to supporting students’ emotions, teachers improving pedagogical effectiveness, teachers improving pedagogical delivery and teachers opening opportunities for interaction between colleagues and administrators. This finding allows various stakeholders to collaborate to improve existing strategies while promoting the innovation agenda in Inclusive Education. In the end, the goals and targets of the Malaysian Ministry of Education in the Malaysian Education Development Plan 2021-2025 through the 3rd wave can be successfully achieved.